Pengaru Pertumbuhan Ekonomi Terhadap Indeks Pembangunan Manusia (IPM) Di Provinsi Sumatera Selatan Tahun 2016-2020 - Tahan Upoyo Trisno; Munajat; Yetty Oktarina (Jurnal Bakti Agribisnis, 2022)
This study aims to determine the effect of economic growth (x), on the human development index (y) in South Sumatra in 2016-2020. The data used is secondary data from the Central Statistics Agency. The analytical method used is panel data regression. The results of the t test show that economic growth (x) has a positive and insignificant effect on the human development index (y). The results of the coefficient of determination test show that the dependent variable can be explained by the independent variable by 32.58% and the remaining 67.42% is explained by other factors outside this model.